14th BSGC2020 - Future Challenges for Geotechnical Engineering Preface. Issue 1 (April 2021) - Unknown
Abstract : The Baltic Sea Region Geotechnical Conference (BSGC) series dates back to 1968, making it one of the oldest regional geotechnical conferences. The 14 th Baltic Sea Region Geotechnical Conference, originally scheduled to take place in Helsinki in May 2020, had to be postponed due to COVID19 pandemic. It finally took place as virtual conference on 18 th -19 th January 2021, arranged in parallel with the 18 th Nordic Geotechnical Meeting (NGM). The conference attracted total of 271 participants from 32 countries, successfully allowing to share insights and discuss ideas related to Future Challenges for Geotechnical Engineering, the main topic of the meeting. This 14 th BSGC proceedings contain 31 technical papers presented during the conference alongside 14 interesting industry presentations. In the proceedings, the papers are divided into sections related to: Soil and rock investigations Digital applications in geotechnics Environmental Geotechnics and recycling Modelling Design experiences and theoretical solutions Ports and foundation engineering Case studies and geotechnical art Furthermore, three keynote speakers presented during the 14 th BSGC. The signature keynote entitled Signatures and impacts of climate change in coastal environments of the Baltic Sea and affiliations was given by Professor Tarmo Soomere, the President of Estonian Academy of Sciences. The other two keynotes were awarded jointly with 18 th NGM. List of Organizing Committee, Scientific Committee are available in the pdf.